2022
DOI: 10.1093/ajcp/aqac119
|View full text |Cite
|
Sign up to set email alerts
|

Strong Coexpression of Transcription Factors PU.1 and Oct-2 in Rosai-Dorfman Disease

Abstract: Objectives Rosai-Dorfman disease (RDD) is a rare disorder characterized by the accumulation of large S100 protein-positive histiocytes that typically exhibit emperipolesis. The recently reported expression of Oct-2 in RDD histiocytes led us to explore whether PU.1, a transcription factor that is required for monocyte and B-cell development, could similarly function as a diagnostic marker in RDD. Methods We evaluated the expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…10 It was reported in 2009 as being positive in Langerhans-cell histiocytosis, reticulohistiocytomas, and xanthogranulomas and more recently, in RDD. 11,12 These authors confirmed the specificity of this marker for histiocytosis by showing its negativity on cutaneous lesions such as dermatofibroma, melanoma, Spitz nevi, and fibrous papules. Our study extended the testing on a larger variety of histiocytoses and we confirmed the positivity of PU.1 in all of them.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…10 It was reported in 2009 as being positive in Langerhans-cell histiocytosis, reticulohistiocytomas, and xanthogranulomas and more recently, in RDD. 11,12 These authors confirmed the specificity of this marker for histiocytosis by showing its negativity on cutaneous lesions such as dermatofibroma, melanoma, Spitz nevi, and fibrous papules. Our study extended the testing on a larger variety of histiocytoses and we confirmed the positivity of PU.1 in all of them.…”
Section: Discussionmentioning
confidence: 71%
“…It is required for the development of Yolk sac‐derived macrophages 10 . It was reported in 2009 as being positive in Langerhans‐cell histiocytosis, reticulohistiocytomas, and xanthogranulomas and more recently, in RDD 11,12 . These authors confirmed the specificity of this marker for histiocytosis by showing its negativity on cutaneous lesions such as dermatofibroma, melanoma, Spitz nevi, and fibrous papules.…”
Section: Discussionmentioning
confidence: 77%
“…RDD diagnosis relies on histopathological examination, characterized by distinctive histiocyte proliferation (positive for S100 protein, oct-2, and cyclin D1) exhibiting emperipolesis (phagocytosed lymphocytes within histiocytes) [ 8 ]. While RDD is often perceived as a tumour and surgically resected, the prognosis is favourable for most patients, with spontaneous resolution observed in 20% of cases [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“… 12 PU.1 has been suggested as a marker for macrophage differentiation in Rosai–Dorfman disease and Erdheim–Chester disease. 13 , 14 PU.1 may be an additional marker for MS showing monocytic and monoblastic differentiation.…”
Section: Discussionmentioning
confidence: 99%